KATA KERJA PELAPORAN PADA ARTIKEL ILMIAH BERBAHASA INDONESIA: STUDI BERBASIS KORPUS - Praminatih, Gusti Ayu (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025)
Amid the dominance of English as a lingua franca in writing scientific texts, Indonesian still exists as the language of writing scientific articles in various fields of science in nationally accredited journals. However, studies exploring Indonesia’s vital role in this context have not received much attention. One of the essential roles of language in scientific texts is as a reporting verb. Reporting verbs introduce, support, refute, and believe someone else’s or one’s ideas to build an argument in a scientific text. This study aims to explore the form, frequency, and function of reporting verbs in scientific articles in the field of linguistics using a corpus linguistics approach. A corpus was built from 64 Indonesian articles published by  Linguistik Indonesia: Jurnal Masyarakat Linguistik Indonesia  to achieve these objectives.   Furthermore, AntConc software was used to obtain the form and frequency of reporting verbs and analyse their function using the theory from (Thompson & Yiyun (1991). This study found that in the last ten years, Indonesian scientific articles have diverse reporting verb forms grouped into five categories: textual reporting verbs, mental reporting verbs, research reporting verbs, comparison reporting verbs, and theorising reporting verbs. There are two verb forms from the textual reporting verb category with the highest frequencies. While comparison reporting verbs have the least forms among other categories. This study also found various forms, frequencies, and functions of reporting verbs. Further, this study provides suggestions for compiling teaching materials, such as a list of reporting verbs specifically for students, writers, and instructors for scientific writing to strengthen Indonesian’s existence in the scientific realm.